2009
DOI: 10.1111/j.1537-2995.2009.02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of transfusional iron overload in patients with myelodysplastic syndrome or severe anemia: data from multicenter clinical practices

Abstract: This study finds only 41% of ICT-eligible patients with lower-risk MDS received ICT in clinical practice, and treatment was initiated later than recommended. Receipt of ICT was associated with significantly longer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…Early results from prospective studies of DFX in LR-MDS patients with IO demonstrated significant reductions in serum ferritin, liver iron concentration and hepatic transaminases within 3-6 months, but these studies had limited follow-up and did not report on survival or organ damage outcomes [21][22][23][24]. ICT has been associated in observational studies with improved survival in MDS patients with IO [5][6][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Early results from prospective studies of DFX in LR-MDS patients with IO demonstrated significant reductions in serum ferritin, liver iron concentration and hepatic transaminases within 3-6 months, but these studies had limited follow-up and did not report on survival or organ damage outcomes [21][22][23][24]. ICT has been associated in observational studies with improved survival in MDS patients with IO [5][6][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an association between iron chelation therapy and longer overall survival was shown in patients with MDS or severe anemia requiring multiple blood transfusions, 32,33 and adequate iron chelation therapy is recommended for such patients. 34 The administration of oral iron-chelating agents such as deferasirox may be an attractive treatment for iron-overloaded patients compared with deferoxamine, which requires s.c. or i.v.…”
Section: Category Bacterial Isolatesmentioning
confidence: 99%
“…35,36 Despite the aforementioned studies, the literature is full of weak attempts to overstate the danger of iron overload in patients with MDS and the unproven value of iron chelation therapy. [37][38][39][40][41][42] Most of these studies inappropriately used serum ferritin as the surrogate for both clinically relevant disease and treatment effect, and some have even flirted with retrospective comparison of patients who have or have not received iron chelation therapy. The fact is that physicians are more likely to administer iron chelation therapy to patients in whom a longer life expectancy is anticipated, and, therefore, nothing short of a prospective randomized study can provide the information needed to justify the use of a potentially toxic and officially expensive form of treatment.…”
Section: Azacitidine and Decitabinementioning
confidence: 99%